2023
DOI: 10.1371/journal.pone.0288063
|View full text |Cite|
|
Sign up to set email alerts
|

Multimorbidity and food insecurity in adults: A systematic review and meta-analysis

Abstract: Food insecurity is one of the main factors affecting multimorbidity. Previous studies have shown that food insecurity may lead to multimorbidity due to person’s inability to consume nutritious diet. However, considering that multimorbidity may cause work-related disabilities and an unstable income, others support the possible effect that multimorbidity has on food insecurity. The purpose of this systematic review and meta-analysis is to examine the relationship between food insecurity and multimorbidity in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
4
0
1
Order By: Relevance
“…These authors also studied the phenomenon of reverse causation to determine whether the presence of multimorbidity (≥2 comorbid conditions) could lead to food insecurity. Using data from 4 studies that included a total of >83,000 adults, they found that individuals with multi-morbidity had more than 2.5 times higher odds of having food insecurity (odds ratio 2.58, 95% CI 1.66-3.49, p < 0.001) when compared to those without multi-morbidity (presence of 0-1 comorbid conditions), although the heterogeneity of the included studies was high (I 2 = 89.7%, p < 0.001) [23]. An analysis of 57,517 adult NHANES participants between 1999-2018 with either known cardiovascular disease (CHD, stroke, CHF) or diseases that confer cardiometabolic risk (hypertension, diabetes, hyperlipidemia, obesity) found that the overall prevalence of food insecurity in this population was 11.8%, but increased over time from 8.2 -10.2% in 1999-2006 to 18.2-18.5% in 2015-2018.…”
Section: Food Insecurity and Cardiovascular Disease -A Bidirectional ...mentioning
confidence: 98%
“…These authors also studied the phenomenon of reverse causation to determine whether the presence of multimorbidity (≥2 comorbid conditions) could lead to food insecurity. Using data from 4 studies that included a total of >83,000 adults, they found that individuals with multi-morbidity had more than 2.5 times higher odds of having food insecurity (odds ratio 2.58, 95% CI 1.66-3.49, p < 0.001) when compared to those without multi-morbidity (presence of 0-1 comorbid conditions), although the heterogeneity of the included studies was high (I 2 = 89.7%, p < 0.001) [23]. An analysis of 57,517 adult NHANES participants between 1999-2018 with either known cardiovascular disease (CHD, stroke, CHF) or diseases that confer cardiometabolic risk (hypertension, diabetes, hyperlipidemia, obesity) found that the overall prevalence of food insecurity in this population was 11.8%, but increased over time from 8.2 -10.2% in 1999-2006 to 18.2-18.5% in 2015-2018.…”
Section: Food Insecurity and Cardiovascular Disease -A Bidirectional ...mentioning
confidence: 98%
“…A pesar de la existencia de los programas internacionales y nacionales, la IA persiste condicionando problemas de salud como lo son las ECNT. 8,36 Según datos de la Organización Mundial de la Salud (OMS), las ECNT representan el 71% de todas las muertes a nivel mundial, lo que equivale en promedio a 41 millones de fallecimientos cada año, con una tendencia ascendente proyectada hacia el año 2030. 5 Mientras persiste esta morbimortalidad de ECNT, coexisten, más de 3 mil millones de personas en todo el mundo con experiencias de algún grado de IA, 9 con un impacto no uniforme entre la población, afectando de manera más significativa a aquellos que residen en zonas rurales, poseen bajos ingresos o forman parte de poblaciones marginadas.…”
Section: Inseguridad Alimentaria Y Enfermedades Crónicas No Transmisi...unclassified
“…In turn, multimorbidity may raise the risk of food insecurity. 5 This could be attributed to increased health care spending as a result of multimorbidity and health care utilization, 6 which finally leads to food insecurity due to resource constraints. Multimorbidity may also potentially increase the likelihood of food insecurity while simultaneously reducing health care utilization.…”
Section: Introductionmentioning
confidence: 99%